Retaining Top Talent (High Potential): Strategies To Reduce Employee Turnover In Companies In Jakarta - Indi Nervilia; Nurwulan Kusuma Devi; Syukrio Idaman; Haspul Naser (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The issue of employee turnover poses a significant challenge for private organizations. However, by implementing effective strategies to improve organizational performance, productivity, and overall success, it is possible to retain employees with high potential. This study conducts an in-depth analysis of employee turnover, identifies contributing factors, recognizes patterns and trends, and provides practical and evidence-based recommendations to help private companies reduce employee turnover and improve their employee retention strategies. The researcher used Structural Equation Modelling (SEM) Smart PLS 4.0, to analyze data on the factors associated with employee turnover. The study's findings may have significant effects on organisational culture by generating more stable and engaged employees. The study suggests that organizational culture, job satisfaction, and retention significantly impact company turnover. This research underscores the importance of understanding and addressing employee turnover in private or state companies to enhance long-term sustainability and competitiveness.